Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1104/pp.109.146928
|View full text |Cite
|
Sign up to set email alerts
|

Probing Allosteric Binding Sites of the Maize Endosperm ADP-Glucose Pyrophosphorylase  

Abstract: Maize (Zea mays) endosperm ADP-glucose pyrophosphorylase (AGPase) is a highly regulated enzyme that catalyzes the rate-limiting step in starch biosynthesis. Although the structure of the heterotetrameric maize endosperm AGPase remains unsolved, structures of a nonnative, low-activity form of the potato tuber (Solanum tuberosum) AGPase (small subunit homotetramer) reported previously by others revealed that several sulfate ions bind to each enzyme. These sites are also believed to interact with allosteric regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Also, a particular behavior was observed in S. coelicolor UDPGlc PPase concerning UTP consumption, since it was not possible to reach a clear plateau for the substrate saturation curves under the assay conditions (even when using up to 20 mM UTP and 50 mM Mg 2ϩ ), from which we estimate a rough V max value for the physiological activity of the enzyme (Table 2). This odd characteristic disagrees with respect to the function of UTP and Mg 2ϩ in catalysis, as it is known for other NDP-Glc PPases that the nucleotide binds first to the enzyme and that the major substrate would be the complex it forms with the divalent cation (6,17,27). However, results reported for the UDP-Glc PPase from Xanthomonas spp.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Also, a particular behavior was observed in S. coelicolor UDPGlc PPase concerning UTP consumption, since it was not possible to reach a clear plateau for the substrate saturation curves under the assay conditions (even when using up to 20 mM UTP and 50 mM Mg 2ϩ ), from which we estimate a rough V max value for the physiological activity of the enzyme (Table 2). This odd characteristic disagrees with respect to the function of UTP and Mg 2ϩ in catalysis, as it is known for other NDP-Glc PPases that the nucleotide binds first to the enzyme and that the major substrate would be the complex it forms with the divalent cation (6,17,27). However, results reported for the UDP-Glc PPase from Xanthomonas spp.…”
Section: Resultsmentioning
confidence: 82%
“…It is noteworthy that neither Glc-6P nor Man-6P was ever reported as the main effector of any bacterial ADP-Glc PPase characterized previously; moreover, this is the first time that an ADP-Glc PPase shows inhibition by NADPH (3, 4). Recently, Boehlein et al (6,7) showed that Fru-6P and Glc-6P are effectors of the maize ADPGlc PPase, both hexose-P activating the enzyme to extents similar to that for (although with higher A 0.5 than) 3-PGA, the primary activator of the plant enzyme. For the maize enzyme, the authors determined an A 0.5 of 4 mM for Glc-6P, which is about 18-fold higher than that corresponding to 3-PGA (6,7).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, residues implicated in the activation of plant enzymes (maize [32] and potato tuber [12]) have been identified in both domains in the protein. Therefore, it seems feasible that 3-PGA could trigger a similar activation mechanism.…”
Section: Resultsmentioning
confidence: 97%
“…tauschii , the “LGGG” motif was present in the N-terminal region. The ATP, ADP, Mg ++ , 3-phosphoglyceric acid (3-PGA), fructose-6-phosphate (F-6-P) and glucose-6-phosphate (G-6-P) ligands are known to bind to the above sites and control the AGPase activity through allosteric and redox modifications (Boehlein et al, 2010). The occurrence of these identified ligand binding aa residues corresponds the similar lignad binding aa residues of potato homotetramer (1YP4), which interacts with ATP (Jin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of these identified ligand binding aa residues corresponds the similar lignad binding aa residues of potato homotetramer (1YP4), which interacts with ATP (Jin et al, 2005). Further, from among the several aa residues involved in the ligand binding sites, arginine has been implicated in controlling the allosteric regulation of maize AGPase (Boehlein et al, 2010). In an earlier study of SS of several monocot and dicot species, five times more ligand binding sites were reported in the ADP_Glucose_PP domain than in the LbH_G1P_AT_C domain (Sarma et al, 2014).…”
Section: Discussionmentioning
confidence: 99%